The Impact of Compensation, Organizational Commitment, and Job Satisfaction on Turnover Intention among Young Female Employees - Muhammad Farid Wajdi; Arni Nafisa (Universitas Muhammadiyah Yogyakarta, 2023)
This study meticulously examined the impact of compensation and organizational commitment on turnover intentions among young female employees, with job satisfaction as a mediating factor. The study's subject pool comprises young female employees aged between 19 and 25 in private healthcare institutions. Data collation entailed employing a Likert scale questionnaire, while the ensuing analysis adopted the Partial Least Squares Structural Equation Modelling (PLS-SEM) approach. The conclusions study proffered that compensation exerted a non-significant negative impact on turnover intentions, concurrently exerting a significant positive influence on job satisfaction. Organizational commitment yielded a notable and negative impact on turnover intentions, simultaneously engendering a marked positive impact on job satisfaction. Curiously, job satisfaction evinced a non-significant negative impact on turnover intentions. Further nuanced analyses revealed that compensation yielded a non-significant negative impact on turnover intentions via the intermediary of job satisfaction. Similarly, organizational commitment's influence on turnover intentions was insignificant when mediated through job satisfaction. This study's seminal contribution discovered that contrary to prevalent assumptions, especially for young female employees, when compensation could provide job satisfaction and is combined with organizational commitment, it will not affect turnover intentions directly or indirectly.